An up-to-date evaluation of sotagliflozin for the treatment of type 1 diabetes. (12th October 2020) - Chatzopoulos, Georgios; Tziomalos, Konstantinos
ABSTRACT: Introduction: The majority of patients with type 1 diabetes mellitus (T1DM) do not achieve glycemic targets. In addition, treatment with insulin is associated with increased risk for hypoglycemia and weight gain. Accordingly, there is an unmet need for new safe and effective glucose-lowering agents in this population. Sotagliflozin, a dual inhibitor of sodium-glucose co-transporters 1 and 2, has been recently approved for use in patients with T1DM. Areas covered: The authors review the major trials that have evaluated the safety and efficacy of sotagliflozin and provide their expert opinion. Expert opinion: Even though sotagliflozin reduces HbA1  c levels and does not appear to increase the risk for hypoglycemia in most patients, the substantially increased risk for diabetic ketoacidosis limits the use of this agent to a carefully selected subgroup of patients with T1DM. Based on the existing evidence, sotagliflozin should be considered only in patients who have failed to achieve adequate glycemic control despite optimal insulin therapy, are at low risk for diabetic ketoacidosis, have been adequately trained to recognize this complication and are able to be in close contact with their physician.